Comparative Cost Analysis of Four Interventions to Prevent HIV Transmission in Bandung, Indonesia - Eveline J.M. Verstraaten; Fenna M.M. Beeren; Jip L.C Janssen; Sophie Kemper; Adiatma Y.M Siregar; Noor Tromp; Rob Baltussen (Acta Medica Indonesiana)
Background: the costs of HIV/AIDS interventions in Indonesia are largely unknown. Knowing these costs is an important input for policy makers in the decision-making of setting priorities among HIV/AIDS interventions. The aim of this analysis is to determine the costs of four HIV/AIDS interventions in Bandung, Indonesia in 2015, to inform the local AIDS commission. Methods: data on utilization and costs of the different interventions were collected in a sexual transmitted infections (STI)-clinic and the KPA, the local HIV/AIDS commission, for the period of January 2015-December 2015. The costs were estimated from a societal perspective, using a micro-costing approach. Results: the total annualized costs for condom distribution, mobile voluntary counselling and testing (VCT), religious based information, communication, and education (IEC) and STI services equalled US$56,926, US$2,985, US$1,963 and US$5,865, respectively. Conclusion: this analysis has provided cost estimates of four different HIV/AIDS interventions in Bandung, Indonesia. Additionally, it has estimated the costs of scaling up these interventions. Together, this provides important information for policy makers vis-à-vis the implementation of these interventions. However, an evaluation of the effectiveness of these interventions is needed to estimate the cost-effectiveness.